The Concept of á¹¢ulá¸¥ and Mediation in Marriage Conflict Resolution in Religious Courts: A Comparative Study between Contemporary Indonesian Family Law and Classical Islamic Law - Bani Syarif Maula (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
Mediation as a dispute resolution process outside the courtroom has been used by the Religious Courts. Its juridical basis is based on Indonesian Supreme Court Regulations Number 2 of 2003 and Number 1 of 2008 concerning Mediation Procedures in Courts. Meanwhile, in the classical Islamic legal tradition, marital conflicts are resolved by a third party outside the courtroom which is referred to as á¹£ulá¸¥, namely efforts to reconcile through a process of taá¸¥kÄ«m or arbitration. Based on this, this study answers the question whether the Religious Courts in Indonesia fully use the concept of á¹£ulá¸¥ as a process of resolving marital conflicts as depicted in the classical Islamic legal tradition. This study concludes that the Religious Courts in Indonesia do not fully use the concept of á¹£ulá¸¥ as a process of resolving marital conflicts as depicted in the classical Islamic legal tradition. This is because the concept of á¹£ulá¸¥ in Islamic law uses the taá¸¥kÄ«m (á¸¥akam) mechanism. The concept of á¸¥akam originating from the classical Islamic legal tradition and mediation originating from the contemporary national legal tradition actually both have substantial differences in terms of concept and implementation in the Religious Courts. The difference in concept is due to differences in sources, authorities, and procedures. However, there are similarities between the two, which lie in the involvement of someone who plays a role in resolving disputes and conflicts in court.